Distribution and factors influencing chickpea wilt and root rot epidemics in Ethiopia. (April 2018) - Yimer, Sultan Mohammed; Ahmed, Seid; Fininsa, Chemeda; Tadesse, Negussie; Hamwieh, Aladdin; Cook, Douglas R.
Abstract: Chickpea is a major food legume crop in the mid-highlands of Ethiopia where its yield is negatively impacted by the wilt and root rot disease complex. The pathogens associated with WRR complex and their associations with biophysical factors have not been well understood in the past. We report here a survey of five major chickpea-growing regions covering 30 districts in the central and northern highlands of Ethiopia. The associations between disease parameters and biophysical factors were assessed using logistic regression analyses. Moreover, pathogens associated with wilt and root rot were identified, and their frequency of occurrence was determined. Mean percent wilt and root rot incidence and percent severity index were the highest in Gojam followed by Gondar and the lowest in Shoa. The major pathogens associated with infected roots were Fusarium oxysporum f. sp. ciceris, Fusarium solani, Rhizoctonia bataticola, Sclerotium rolfsii, and Rhizoctonia solani . The most frequently isolated pathogen was F. oxysporum f. sp. ciceris followed by R. solani . Moreover, significant (P < .001) associations between disease parameters and planting date and between weeding practice and soil and chickpea types were observed. High disease incidence and percent severity index showed high probability of association with planting date and chickpea types. Desi chickpea and chickpea that were planted early in the season had approximately 2 and 9 times greater probability of experiencing a high disease incidence and a 6–5 times greater probability of experiencing high wilt and root rot severity, respectively. High disease incidence and percent severity index were also correlated with weed infestation and planting on heavy black soils. Therefore, late planting, appropriate weeding, and the use of chickpea cultivars with a high level of resistance are important options to manage WRR complex. Highlights: Wilt and root rot (WRR) disease complex are major chickpea production constraints. High WRR incidence observed across all surveyed fields. WRR is significantly associated with sowing date, soil type, chickpea type and weeding practices. The major pathogen associated with WRR is Fusarium oxysporium f. sp. ciceris . Integrated management is recommended to manage WRR.